Safety and tracking of intrathecal allogeneic mesenchymal stem cell transplantation in healthy and diseased horses - Barberini, Danielle Jaqueta; Aleman, Monica; Aristizabal, Fabio; Spriet, Mathieu; Clark, Kaitlin C.; Walker, Naomi J.; Galuppo, Larry D.; Amorim, Rogério Martins [UNESP]; Woolard, Kevin D.; Borjesson, Dori L. (My University, 2018)
Background: It is currently unknown if the intrathecal administration of a high dose of allogeneic mesenchymal stem cells (MSCs) is safe, how MSCs migrate throughout the vertebral canal after intrathecal administration, and whether MSCs are able to home to a site of injury. The aims of the study were: 1) to evaluate the safety of intrathecal injection of 100 million allogeneic adipose-derived MSCs (ASCs); 2) to assess the distribution of ASCs after atlanto-occipital (AO) and lumbosacral (LS) injection in healthy horses; and 3) to determine if ASCs homed to the site of injury in neurologically diseased horses. Methods: Six healthy horses received 100 × 106 allogeneic ASCs via AO (n = 3) or LS injection (n = 3). For two of these horses, ASCs were radiolabeled with technetium and injected AO (n = 1) or LS (n = 1). Neurological examinations were performed daily, and blood and cerebrospinal fluid (CSF) were evaluated prior to and at 30 days after injection. Scintigraphic images were obtained immediately postinjection and at 30 mins, 1 h, 5 h, and 24 h after injection. Three horses with cervical vertebral compressive myelopathy (CVCM) received 100 × 106 allogeneic ASCs labeled with green fluorescent protein (GFP) via AO injection and were euthanized 1-2 weeks after injection for a full nervous system necropsy. CSF parameters were compared using a paired student's t test. Results: There were no significant alterations in blood, CSF, or neurological examinations at any point after either AO or LS ASC injections into healthy horses. The radioactive signal could be identified all the way to the lumbar area after AO ASC injection. After LS injection, the signal extended caudally but only a minimal radioactive signal extended further cranially. GFP-labeled ASCs were not present at the site of disease at either 1 or 2 weeks following intrathecal administration. Conclusions: The intrathecal injection of allogeneic ASCs was safe and easy to perform in horses. The AO administration of ASCs resulted in better distribution within the entire subarachnoid space in healthy horses. ASCs could not be found after 7 or 15 days of injection at the site of injury in horses with CVCM.
Keywords: Adipose tissue; Cerebrospinal fluid; Intrathecal; Mesenchymal stem cells; Neurology; Scintigraphy